Effects of 5-Fluorouracil on the Expression of Epigenetic Enzymes and Promoter Methylation of Selected Genes in Monolayer and Spheroid Cultures of Colorectal Cancer Cells - Maryam Niknam; Masoumeh Varedi; Mozhdeh Zamani; Pooneh Mokarram; Fakhraddin Naghibalhossaini (Tabriz University of Medical Sciences, 2024)
Background: Emerging evidence suggests that epigenetic mechanisms contribute to 5-fluorouracil (5-FU) resistance in colorectal cancer (CRC). However, there is limited research on the direct impact of 5-FU on epigenetic alterations in CRC. This study aimed to investigate how 5-FU treatment affects the expression of enzymes involved in epigenome regulation and promoter DNA methylation in human CRC cells. Methods: The viability of CRC cell lines (SW48, HCT116, LS180, and HT29) was evaluated after 48 hours of 5-FU treatment using MTT assay in both monolayer and hanging drop spheroid cultures. The cells were treated with an IC20 concentration of 5-FU and then the relative expressions of histone deacetylases (HDAC) and DNA methyltransferas1 (DNMT1) in 5-FU-treated and untreated cells were measured by quantitative RT-PCR (qRT-PCR). The status of promoter methylation of selected genes was analyzed using the methylation-specific PCR (MSP) method. Results: The 3D cultures of cells were more resistant to 5-FU than their 2D counterparts. The effect of 5-FU on HDAC1 expression was greater in 3D cultures compared to 2D cultures. 5-FU downregulated SIRT1 and DNMT1 in 2D culture of HCT116 and SW48 and upregulated them in 3D cultures of HT29 and LS180 cells. In both monolayer and spheroid cultures, 5-FU downregulated HDAC2 in HCT116, LS180, and HT29 and HDAC4 in HCT116, LS180, and SW48 cells. 5-FU primarily changed promoter methylation in monolayer cultures. Conclusion: The epigenetic response to 5-FU is cell line-specific and depends on the culture method. 5-FU modulates epigenome in CRC cells by regulating DNMT1 and HDAC expressions. 3D cultures were found to be considerably more resistant to 5-FU-induced cytotoxicity and promoter DNA methylation changes than 2D cultures. 5-FU downregulated HDAC and DNMT1, particularly in the drug-sensitive cells, and increased the levels of DNMT1 in the drug-resistant cells.